2020
DOI: 10.1111/acel.13144
|View full text |Cite|
|
Sign up to set email alerts
|

Mossy cell synaptic dysfunction causes memory imprecision via miR‐128 inhibition of STIM2 in Alzheimer's disease mouse model

Abstract: Recently, we have reported that dentate mossy cells (MCs) control memory precision via directly and functionally innervating local somatostatin (SST) inhibitory interneurons. Here, we report a discovery that dysfunction of synaptic transmission between MCs and SST cells causes memory imprecision in a mouse model of early Alzheimer's disease (AD). Single‐cell RNA sequencing reveals that miR‐128 that binds to a 3′UTR of STIM2 and inhibits STIM2 translation is increasingly expressed in MCs from AD mice. Silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…miRNAs regulating NMDAR expression have also been reported, for instance, miR-139-5p [ 77 ] and miR-125b [ 78 ] have been involved in synaptic plasticity regulation by binding to mRNA coding for NR2A subunit while miR-539 and miR-34a regulate NR2B subunit of NMDAR [ 79 , 80 ]. Moreover, indirect regulation of NMDAR through miR-128 binding to STIM2 (stromal interaction molecule 2) has also been suggested as a miRNA-mediated mechanism of synaptic plasticity modulation [ 81 ].…”
Section: Mirnas As Mediators Of Synaptic Dysfunction In Admentioning
confidence: 99%
“…miRNAs regulating NMDAR expression have also been reported, for instance, miR-139-5p [ 77 ] and miR-125b [ 78 ] have been involved in synaptic plasticity regulation by binding to mRNA coding for NR2A subunit while miR-539 and miR-34a regulate NR2B subunit of NMDAR [ 79 , 80 ]. Moreover, indirect regulation of NMDAR through miR-128 binding to STIM2 (stromal interaction molecule 2) has also been suggested as a miRNA-mediated mechanism of synaptic plasticity modulation [ 81 ].…”
Section: Mirnas As Mediators Of Synaptic Dysfunction In Admentioning
confidence: 99%
“…The type of interneuron that MCs innervate was first proposed to be the basket cell (Sloviter, 1991;Sloviter, 1994) and then other studies used the term "perisomatictargeting" for interneurons that included basket-cells and others, such as axo-axonic cells (Freund and Gulyas, 1997). More recently it has been suggested that MCs activate several interneuron cell types (Hsu et al, 2015) and one is the dendritic-targeting HIPP cell (Deng et al, 2020).…”
Section: B the Gabaergic Neuron Subtype Underlying Optogenetically-ementioning
confidence: 99%
“…miR-128, a highly enriched miRNA in the CNS, 81 regulates neuronal proliferation and differentiation in the developing neocortex 82 and neuronal excitability in vitro. 83 miR-128 is also involved in multiple neurobiological diseases, such as hypoxic-ischemic brain damage, 84 Alzheimer disease, 85 and spinal cord injury. 86 miR-128 is encoded by two separate genes, miR-128-1 and miR-128-2 genes.…”
Section: Mir-128mentioning
confidence: 99%